PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS XI - ., Febriyani (Jurnal Edukasi dan Penelitian Matematika, 2023)
Mathematical Problem-solving is one of the abilities that needs to be developed in learning mathematics. However, that ability is still low in class XI SMAN 7 Padang is still low. One solution to overcome the problem is used a cooperative learning model of Group Investigation (GI). This research type were descriptive and quasi-experiment with a research design of Nonequivalent Posttest-Only Control Group Design. The sample are Class XI F6 as the experiment class and Class XI F7 as the control class. Based on result of data analysis acquired P-value = 0.000 where P-value < 0.05. It can be concluded that mathematical problem-solving skills on students who learn with a cooperative learning model of GI is better than direct learning. Keywords – Cooperative Learning, Direct Learning, Group investigation, Mathematical Problem Solving